Retrospective evaluation of adverse events of neoadjuvant or induction chemotherapy with docetaxel, cisplatin, and 5-fluorouracil in esophageal squamous cell carcinoma - Sugawara, Mitsuhiro; Katada, Chikatoshi; Katada, Natsuya; Takahashi, Kaoru; Higuchi, Katsuhiko; Komori, Shouko; Moriya, Hiromitsu; Ishiyama, Hiromichi; Yamashita, Keishi; Sakuramoto, Shinichi; Tanabe, Satoshi; Koizumi, Wasaburo; et al. (Esophagus : official journal of the Japan Esophageal Society, 2013)
Background Neoadjuvant or induction chemotherapy with docetaxel, cisplatin, and 5-fluorouracil (DCF) is regarded as one of the most promising regimens for locally advanced esophageal squamous cell carcinoma (ESCC), but has a high incidence of adverse events. We retrospectively evaluated adverse events in patients with ESCC who received DCF. Methods Between December 2009 and May 2012, 57 patients with Stage II to IV locally advanced ESCC received three cycles of DCF (docetaxel 70–75 mg/m 2 , day 1; cisplatin 70–75 mg/m 2 , day 1; 5-fluorouracil, 750 mg/m 2 , days 1–5) as neoadjuvant or induction chemotherapy in a single institution. Adverse events of DCF were evaluated retrospectively. Results The median age of the subjects was 65 years (range 41–74). Fifty-four patients (95 %) received three cycles of DCF as scheduled. Dose modifications were made for 34 patients (60 %). There were no treatment delays or unplanned admissions. Grade 3 or 4 neutropenia developed in 53 patients (93 %), including 18 (32 %) with febrile neutropenia. Other grade 3 or 4 toxic effects were hyponatremia in 15 patients (26 %), hypokalemia in 10 (18 %), oral mucositis in 9 (16 %), diarrhea and hypocalcemia in 8 (14 %) each, fatigue in 4 (7 %), and vomiting, anorexia, hiccups, hypoalbuminemia, and elevations of alanine aminotransferase in 1 (2 %) each. No treatment-related deaths occurred within 30 days after completion of DCF. Conclusions For patients with locally advanced ESCC, neoadjuvant or induction chemotherapy with DCF is tolerable. DCF is a viable treatment option for fit patients with locally advanced ESCC.